Mental (Dis)Order in Later Medieval Europe - Katajala-Peltomaa, Sari; Niiranen, Susanna (Later Medieval Europe, 2014)
Mental (Dis)order in the Late Middle Ages sketches the boundaries between mental, social and physical order and various states of disorder - unexpected mood swings, fury, melancholy, stress, insomnia, and demonic influence - and focuses on the interaction between lay and elite cultures.; Readership: All those interested in medieval culture; the medical, religious, intellectual, social, and art history of late medieval Europe.